Digitalisation in insurance companies - Komarova, K. O. (My University, 2021)
To maintain the stable operation of insurance companies, it is necessary to develop new and improve existing sales channels of insurance products. Helping to expand the insurance market today is to use the information and computer technologies potential.
Keywords: insurance companies; digitalization; possibilities of IT